What Islamic Education Teachers Need To Know and Be Able To Do To Teach Students Higher-Order Thinking Skills? - Neneng Kurnia Rahma Putri; Caly Setiawan (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2022)
Islamic education is said to have less relevance with today's social change in society or does not provide an illustration of the sociocultural context, so students do not appreciate religious values as values that exist in everyday life. This phenomenon requires Islamic education teachers to adopt a teaching approach focusing on higher-order thinking skills (HOTS). Unfortunately, not many Islamic education teachers understand such an approach and how to implement it in their classrooms. This article is a library research study using a content analysis approach. The purpose of this article was to review the literature on HOTS and to offer Islamic education teachers the possibilities and pitfalls of employing this approach. The literature review results show that the basic thing that Islamic education teachers need to do in the 21st century is to change the orientation of their learning from Teacher Centered Learning (TCL) to Student Center Learning (SCL). Islamic education teachers need to prepare and pay attention to various aspects of implementing HOTS-based learning, from planning activities to assessment activities, which must be carried out according to the implementation procedure.